Fostering Communities of Transformation in STEM Higher Education A Multi-institutional Collection of DEI Initiatives - Briganti, Jonathan S.; Sible, Jill C.; Brown, Anne M. (Open textbook library., 2024)
Dive into the multifaceted landscape of inclusive excellence in STEM education with Fostering Communities of Transformation in STEM Higher Education. This scholarly work examines transformative initiatives from Virginia Tech, Radford University, Trinity Washington University, and Towson University, showcasing their role as catalysts in cultivating inclusive excellence across diverse STEM disciplines. Take inspiration from their projects and guidance from their lessons learned with this collection.